Profitability, Liquidity, and Company Size Ratios on Bond Ratings in Banking Companies - Mubarok, Akhmad Yasir; Sapruwan, Muhamad; Dasman, Sunita; Khotimah, Khusnul; Arfa, Iqbal; Wiharti, Wiharti (Lentera Ilmu Nusantara, 2023)
Bond rating is an indicator of timeliness of payment of principal interest and bond payable. Previous research on the factor that affect bond rating still has some research gap, therefore it is necessary to re-examine the factor that affect bond rating. These studies aim to determine the effect of profitability, liquidity and firm size on bond rating in banking companies listed in IDX 2016- 2021. This type of research is quantitative research. The population used in the research are 37 banking companies listed on IDX 2016-2021. The sample collection technique used in this study is purposive sampling, wich resulted in 12 banking companies. The analysis technique used in this study was panel data analysis with the program Eviews 12. Based on the result of the study, it is shown that parallel, profitability and liquidity have no effect on bond rating, while company size have a positive significant.